Degradation of organic pollutants by ultraviolet/ozone in high salinity condition: Non-radical pathway dominated by singlet oxygen. (April 2021) - Wang, Jie; Liu, Haibao; Ma, Defang; Wang, Yan; Yao, Guangping; Yue, Qinyan; Gao, Baoyu; Wang, Shue; Xu, Xing
Abstract: In this work, the combined ultraviolet ozone process (UV/O3 ) was applied for organic contaminant (Reactive Blue K-GL, RB) degradation in high salinity. The degradation rates of RB in both O3 and UV/O3 systems were enhanced by NaCl (the k increased from 0.080 to 0.116 to 0.132 and 0.267 min −1 respectively), while mineralization rate varied at different salt conditions. In addition, UV irradiation promoted the degradation efficiency of RB with the presence of salt. Singlet oxygen ( 1 O2 ) was the primary active species in the UV/O3 system. The quenching experiments and signal intensity of 1 O2 corresponded well to the mineralization of RB. Under conditions of high salinity and high pH, O3 has high mass transfer coefficient (kLa, 3.303 min −1 ) and self-decomposition (kd, 0.600 min −1 ), which further promoted the formation of 1 O2 for mineralization of RB. Furthermore, UV/O3 system was efficient in real textile wastewater treatment (CODCr removal rate 91.7% and decolorization rate 98.7%). Graphical abstract: Image 1 Highlights: UV/O3 technology was efficient in the reactive blue K-GL (RB) and real textile wastewater treatment. Degradation of RB was enhanced by co-existing salt (NaCl). 1 O2 was the primary active specie both in O3 and UV/O3 system. NaCl and alkaline environment enhanced the mass transfer coefficient and self-decomposition of O3 .